Serum increase and liver overexpression of carbohydrate 19.9 antigen in patients with genetic haemochromatosis. Issue 8 (August 1994) - Deugnier, Y M; Rabot, A F; Guyader, D; Moirand, R; Turlin, B; Boucher, E; Lebert, P; Brissot, P
Abstract : CA 19.9 antigen is mainly secreted by biliary and pancreatic duct cells. Its metabolism could be modified in genetic haemochromatosis by iron accumulation within these cells. Therefore, CA 19.9 was assayed in the serum samples of 84 patients with genetic haemochromatosis before and after iron depletion and immunolocalised in the liver of 24 untreated genetic haemochromatosis cases. The study showed that serum CA 19.9 (N < 37 IU/l) was increased (SD) before treatment (41.2 (34)) when compared with after the venesection period (16 (12)), and correlated, before treatment, with the amount of iron excess, transaminases, fibrosis, and biliary iron deposits. Hepatic CA 19.9 was located within the cytoplasm of bile duct and cholangiolar cells. In conclusion, this study shows that a mild, reversible, and non-specific increase in serum CA 19.9 is common in genetic haemochromatosis patients and shows that this increase is related to iron excess, directly or through associated liver damage. The unexplained finding of a mild increase in serum CA 19.9 should lead, in a patient with no diagnosis, to the search for liver iron overload, and, in a patient with untreated genetic haemochromatosis, not to further diagnostic procedures unless this finding persists after completion of the venesection treatment.